Insect diversity and composition during the wet and dry seasons in three forest types of Johor, Malaysia - Siddiki, Aishatu (2015)
The insect diversity and abundance in three forest types namely: Endau Rompin (pristine lowland forest) Gunung Ledang (pristine highland forest) and Bukit Soga (degraded lowland forest) in Johor, Malaysia were studied. The study focused on 10 common insect orders. The objectives are (1) to investigate the composition and abundance of insect morphospecies in three forest types; (2) to compare the composition and abundance of insect morphospecies in the wet and dry seasons in three forest types; and (3) to determine the dominant insect of the study sites. There were four sampling methods employed as baited pitfall traps, aerial net, manual collection and sweep net. The sampling methods were employed three days in each location. The different insects sampled, were higher during the wet season as compared to the dry season (diversity and abundance). Although Bukit Soga lowland a degraded forest had the highest diversity of 52; and abundance of 112,081 individuals, it had the lowest Shannon weiner index of species diversity and lowest evenness of (H’1.09 and evenness of 0.28). Gunung Ledang, had lowest species diversity of 32 and abundance of 1,695 individuals but had the highest H’of 2.34 and highest evenness of 0.68. Endau Rompin had 46 species diversity and abundance of 70,821individuals and H’of 1.17and evenness of 0.30. In highland forest the most diverse dominant insects were the butterflies (Lepidoptera: Rhopalocera). Meanwhile ant, (Hymenoptera: Formicidae) was more diverse in lowland forest than the highland forest. In all the three locations, ant was most abundant. Since Jaccard similarity index was low between Gunung Ledang and Bukit Soga (0.22); and between Gunung Ledang and Endau Rompin (0.27) it is concluded that altitude had a greater effect on insect diversity. This is supported by a two ways ANOVA analyses that showed insect diversity and abundance between the two lowland forests (Endau Rompin and Bukit Soga) and highland forest (Gunung Ledang) are significantly different. Difference between the lowland forests was not significant. Generally, effect of wet and dry seasons has no clear impact on diversity but abundance was higher during wet season especially for ants (Hymenoptera: Formicidae).